Tin selenide-nitrogen doped carbon nanotube composite material and preparation method thereof, lithium ion battery negative electrode sheet and lithium ion battery
Through the preparation of tin selenide-nitrogen doped carbon nanotube composite material, the problems of low specific capacity, poor rate performance and short cycle life of lithium-ion battery negative electrode materials are solved, and battery materials with high specific capacity, excellent rate performance and long cycle life are achieved.
Patent Information
- Application Number
- CN202211268286.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-10-17
AI Technical Summary
The negative electrode materials of existing lithium-ion batteries have low specific capacity, poor rate performance and short cycle life, which cannot meet the development needs of high-specific energy lithium-ion batteries.
The tin selenide-nitrogen doped carbon nanotube composite material is used as the negative electrode material and prepared by step-by-step chemical synthesis method, including generating MnO2 nanowires, coating tin dioxide, forming polydopamine-coated nanotubes, and forming nitrogen-doped carbon nanotubes and tin selenide by baking.
It significantly improves the specific capacity, rate performance and cycle life of tin selenide-nitrogen doped carbon nanotube composite materials, and is suitable for high-energy density lithium-ion batteries.
Smart Images

Figure CN115602834B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to a tin selenide-nitrogen doped carbon nanotube composite material and a preparation method thereof, a lithium ion battery negative electrode sheet and a lithium ion battery. Background Art
[0002] Rechargeable lithium-ion batteries have excellent properties such as small size, light weight, high energy density, long cycle life, good safety performance, low self-discharge and fast charging and discharging. They have been widely used in energy storage devices such as new energy vehicles and various portable electronic products.
[0003] At present, the research on lithium-ion batteries is mainly focused on improving the energy density, cycle stability and service life of lithium-ion batteries, and the negative electrode material of lithium-ion batteries is one of the most critical factors. Currently, the negative electrode material of commercial lithium-ion batteries is basically graphite. However, as a negative electrode material for lithium-ion batteries, the theoretical specific capacity of graphite is only 372mAh·g -1 , resulting in a relatively low energy density of lithium-ion batteries. In addition, the lithium deintercalation potential of graphite is relatively low, and lithium dendrites are easily precipitated, which poses a great safety hazard when used. With the increasing requirements for the energy density of lithium-ion batteries in recent years, graphite negative electrodes can no longer meet the development needs of high-energy lithium-ion batteries. Therefore, exploring and developing new high-capacity negative electrode materials has become an urgent need.
[0004] Metal selenide materials have the advantages of high theoretical specific capacity and low cost, and are a class of anode materials for next-generation lithium-ion batteries with great application prospects. Among them, SnSe can be used as anode materials for lithium-ion batteries due to its special layered crystal structure and high conductivity, and its theoretical specific capacity can reach 1000mAh·g -1 , which makes SnSe have potential advantages and application prospects in electrochemical energy storage. However, SnSe negative electrode materials also have disadvantages. Its volume will change greatly during the charge and discharge process, resulting in the destruction of the electrode structure and the surface solid electrolyte interface film, and the rapid decay of the electrode capacity and cycle performance. In addition, the charge and discharge intermediate product Li2Se of SnSe has poor conductivity, which hinders the transfer of charge, resulting in low electrochemical reaction activity of SnSe, affecting the storage capacity and stability of SnSe. Summary of the invention
[0005] The present invention provides a tin selenide-nitrogen doped carbon nanotube composite material and a preparation method thereof, a lithium ion battery negative electrode sheet and a lithium ion battery, which are used to overcome the defects of lithium ion battery negative electrode materials in the prior art, such as low specific capacity, poor rate performance and short cycle life.
[0006] To achieve the above object, the present invention also provides a method for preparing a tin selenide-nitrogen doped carbon nanotube composite material, comprising the following steps:
[0007] S1: weighing manganese salt and ammonium salt, respectively preparing aqueous solutions, then pouring the ammonium salt solution into the manganese salt solution, stirring thoroughly, heating in a reactor to react, and obtaining MnO2 nanowires;
[0008] S2: dispersing the MnO2 nanowires in a mixed solution of water and ethanol, respectively adding a urea aqueous solution and a stannate aqueous solution, stirring sufficiently, and heating in a reactor to react, thereby obtaining MnO2@SnO2 (tin dioxide coated manganese dioxide) nanowires;
[0009] S3: dispersing the MnO2@SnO2 nanocable in a tris(hydroxymethyl)aminomethane aqueous solution, adding dopamine hydrochloride, stirring thoroughly, and centrifuging to obtain MnO2@SnO2@PDA (polydopamine-coated MnO2@SnO2) nanocable;
[0010] S4: dispersing the MnO2@SnO2@PDA nanocable in an oxalic acid solution, allowing the solution to stand, and centrifuging to obtain SnO2@PDA (polydopamine coated tin dioxide) nanotubes;
[0011] S5: Grind and mix the SnO2@PDA nanotubes and Se powder according to a mass ratio, and calcine in a mixed atmosphere of H2 / Ar to obtain a tin selenide-nitrogen doped carbon nanotube composite material (SnSe@NCNTs).
[0012] To achieve the above object, the present invention further provides a tin selenide-nitrogen doped carbon nanotube composite material, which is prepared by the above-mentioned preparation method.
[0013] To achieve the above objectives, the present invention also proposes a negative electrode plate for a lithium-ion battery, wherein the negative electrode plate is composed of a negative electrode material, superconducting carbon, and a binder in a mass ratio of 80:10:10, and the negative electrode material is the tin selenide-nitrogen-doped carbon nanotube composite material prepared by the preparation method of the tin selenide-nitrogen-doped carbon nanotube composite material described above or the tin selenide-nitrogen-doped carbon nanotube composite material described above.
[0014] To achieve the above objectives, the present invention also proposes a lithium-ion battery, which is mainly composed of a negative electrode plate, an electrolyte, a separator and a metal lithium plate, and the negative electrode plate is the negative electrode plate of the lithium-ion battery described above.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. The preparation method of the tin selenide-nitrogen doped carbon nanotube composite material provided by the present invention comprises the following steps: firstly, manganese salt and ammonium salt are selected as raw materials to obtain MnO2 nanowires, so as to provide a template for the formation of the tin selenide-nitrogen doped carbon nanotube composite material; then, the MnO2 nanowires are dispersed in a mixed solution of water and ethanol, and a urea aqueous solution and a stannate aqueous solution are sequentially added to the MnO2 nanowire dispersion in a dropwise manner to obtain tin dioxide coated manganese dioxide (MnO2@SnO2) nanocables; the MnO2@SnO2 nanocables are dispersed in a tris(hydroxymethyl)aminomethane aqueous solution to obtain polydopamine ( The invention discloses a method for preparing a polydopamine-coated tin dioxide (SnO2@PDA)-coated MnO2@SnO2 nanocable (MnO2@SnO2@PDA); the MnO2@SnO2@PDA nanocable is then dispersed in an oxalic acid aqueous solution to remove the MnO2 by etching, thereby obtaining a polydopamine-coated tin dioxide (SnO2@PDA) nanotube having a hollow structure; finally, the PDA@SnO2 nanotube is mixed with selenium powder, and the polydopamine is decomposed and carbonized to form nitrogen-doped carbon nanotubes by roasting, while tin dioxide and selenium powder react at high temperature to form tin selenide (SnSe), and the tin selenide is dispersed inside the nitrogen-doped carbon nanotubes. The preparation method provided by the invention is environmentally friendly and pollution-free, and the prepared tin selenide-nitrogen-doped carbon nanotube composite material has excellent performance.
[0017] 2. The tin selenide-nitrogen doped carbon nanotube composite material provided by the present invention, the presence of nitrogen doped carbon nanotubes can significantly improve the electronic conductivity of the tin selenide-nitrogen doped carbon nanotube composite material, and the nitrogen doped carbon nanotubes with a hollow structure can significantly buffer the volume expansion effect of tin selenide during the charge and discharge process, thereby improving the service life of the tin selenide-nitrogen doped carbon nanotube composite material; the tin selenide-nitrogen doped carbon nanotube composite material has a porous structure, which is conducive to Li + Conducted at the interface, this allows the electrolyte to fully enter the interior of the tin selenide-nitrogen doped carbon nanotube composite material, thereby improving the rate performance of the tin selenide-nitrogen doped carbon nanotube composite material; a large number of extremely small selenides are dispersed inside the carbon nanotubes of the tin selenide-nitrogen doped carbon nanotube composite material, which can significantly improve the specific capacity of the tin selenide-nitrogen doped carbon nanotube composite material. Therefore, the tin selenide-nitrogen doped carbon nanotube composite material SnSe@NCNTs provided by the present invention has a high specific capacity, excellent rate performance, and a long cycle life, and can be well applied to lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0019] Figure 1 is the XRD pattern of the tin selenide-nitrogen doped carbon nanotube composite material SnSe@NCNTs in Example 1;
[0020] Figure 2 The SEM images of the SnSe@NCNTs composite material of tin selenide-nitrogen doped carbon nanotubes in Example 1; wherein (a) to (d) are SEM images at different magnifications, respectively;
[0021] Figure 3 The SnSe@NCNTs composite material of SnSe-nitrogen doped carbon nanotubes in Example 1 was prepared at 0.1A·g -1 Charge and discharge curves under current density;
[0022] Figure 4 It is a rate performance curve diagram of the tin selenide-nitrogen doped carbon nanotube composite material SnSe@NCNTs and the tin selenide SnSe negative electrode material in Example 1;
[0023] Figure 5 This is a cycle performance diagram of the tin selenide-nitrogen doped carbon nanotube composite material SnSe@NCNTs and the tin selenide SnSe negative electrode material in Example 1.
[0024] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0027] Unless otherwise specified, all drugs / reagents used were commercially available.
[0028] The present invention provides a method for preparing a tin selenide-nitrogen doped carbon nanotube composite material, the preparation method comprising:
[0029] S1: weighing manganese salt and ammonium salt, respectively preparing aqueous solutions, then pouring the ammonium salt solution into the manganese salt solution, stirring thoroughly, heating in a reactor to react, and obtaining MnO2 nanowires;
[0030] Manganese salt and ammonium salt are selected as raw materials to finally obtain the manganese dioxide nanowire structure.
[0031] Under stirring conditions, pour the ammonium salt aqueous solution into the manganese salt solution, continue stirring for 10 to 60 minutes, transfer the mixed solution to a reactor, and place it in an oven for reaction.
[0032] Preferably, the aqueous solution is prepared using deionized water to avoid the introduction of other impurity elements.
[0033] Preferably, the manganese salt is one or more of manganese nitrate Mn(NO3)2, manganese chloride MnCl2, manganese carbonate MnCO3, manganese acetate Mn(CH3COO)2, manganese sulfate MnSO4, manganese hypophosphite Mn(PO2)2, manganese perchlorate Mn(ClO4)2, potassium permanganate KMnO4 and manganese acetylacetonate Mn[CH3COCH=C(O)CH3]2; the ammonium salt is one or more of ammonium sulfate (NH4)2SO4, ammonium carbonate (NH4)2CO3, ammonium nitrate NH4NO3, ammonium fluoride NH4F, ammonium chloride NH4Cl, ammonium bromide NH4Br, ammonium iodide NH4I, ammonium bicarbonate NH4HCO3 and ammonium bisulfate NH4HSO4.
[0034] Preferably, the manganese salt concentration in the manganese salt solution is 0.02-0.05 mol / L; the ammonium salt concentration in the ammonium salt solution is 0.02-0.05 mol / L; the heating reaction temperature is 160-220° C., and the time is 8-36 hours. Appropriate reaction conditions are controlled to ensure that manganese dioxide with a nanowire structure is obtained.
[0035] S2: Dispersing the MnO2 nanowires in a mixed solution of water and ethanol, respectively adding urea aqueous solution and stannate aqueous solution, stirring sufficiently, and heating in a reactor to react, thereby obtaining MnO2@SnO2 nanowires.
[0036] Preferably, the mixed solution is a mixed solution of water and ethanol in a volume ratio of 1:1 to 1:3; the ratio of the MnO2 nanowire to the mixed solution is 100 mg: 20 to 40 mL; the concentration of urea in the reaction solution of the heating reaction is 0.2 to 0.8 mol / L; the concentration of stannate in the reaction solution of the heating reaction is 0.01 to 0.03 mol / L; the temperature of the heating reaction is 150 to 200°C, and the time is 1 to 3 hours. Control the appropriate reaction conditions to ensure that tin dioxide is evenly coated on the surface of the manganese dioxide nanowire to obtain MnO2@SnO2 nanowires.
[0037] S3: Dispersing the MnO2@SnO2 nanocable in a tris(hydroxymethyl)aminomethane (Tris) aqueous solution, adding dopamine hydrochloride, stirring thoroughly, and centrifuging to obtain MnO2@SnO2@PDA nanocable.
[0038] Preferably, the mass ratio of the MnO2@SnO2 nanocable to dopamine hydrochloride is 1:3 to 3:1; the ratio of the MnO2@SnO2 nanocable to tris(hydroxymethyl)aminomethane solution is 100 mg:50 to 200 mL, and the concentration of the tris(hydroxymethyl)aminomethane solution is 0.005 to 0.05 mol / L; and the sufficient stirring time is 2 to 24 h.
[0039] S4: dispersing the MnO2@SnO2@PDA nanocables in an oxalic acid solution, allowing the solution to stand, and centrifuging to obtain SnO2@PDA nanotubes.
[0040] Preferably, the concentration of the oxalic acid solution is 0.2-1.2 mol / L; the ratio of the MnO2@SnO2@PDA nanocable to the oxalic acid solution is 100 mg:50-200 mL; and the standing time is 0.5-12 hours. The standing time is controlled to ensure that the original nanostructure is not destroyed while the MnO2 is etched away, so as to obtain the SnO2@PDA nanotube.
[0041] S5: Grind and mix the SnO2@PDA nanotubes and Se powder according to a mass ratio, and calcine them in a mixed atmosphere of H2 / Ar to obtain a tin selenide-nitrogen doped carbon nanotube composite material (SnSe@NCNTs).
[0042] The polydopamine is decomposed and carbonized to form nitrogen-doped carbon nanotubes by calcination, and tin dioxide reacts with selenium powder to form tin selenide, which is dispersed in the nitrogen-doped carbon nanotubes.
[0043] Preferably, the mass ratio of the SnO2@PDA nanotubes to selenium powder is 3:1 to 1:3; the protective atmosphere is a hydrogen-argon mixed atmosphere, and the volume ratio of hydrogen to argon is 1:9; and calcination is performed in an inert atmosphere to avoid oxidative decomposition of nitrogen-doped carbon nanotubes and tin selenide.
[0044] The calcination is specifically carried out by heating from room temperature to 200-400°C at a rate of 1-10°C / min, and calcining for 1-4h; then heating from 200-400°C to 600-900°C at a rate of 1-10°C / min, and calcining for 1-4h. Appropriate calcination conditions can ensure the preparation efficiency while ensuring the product quality. If the calcination temperature is too high or the time is too long, the tin selenide-nitrogen doped carbon nanotube composite material will be deformed and the particles will become larger; if the calcination temperature is too low or the time is too short, the selenization will be insufficient, impurities will be generated, and the polydopamine will not be completely decomposed.
[0045] The present invention also provides a tin selenide-nitrogen doped carbon nanotube composite material, wherein the tin selenide negative electrode material is prepared by the above-mentioned preparation method.
[0046] The present invention also proposes a negative electrode plate for a lithium-ion battery, which is composed of a negative electrode material, superconducting carbon, and a binder in a mass ratio of 80:10:10, and the negative electrode material is a tin selenide-nitrogen-doped carbon nanotube composite material prepared by the preparation method of the tin selenide-nitrogen-doped carbon nanotube composite material described above.
[0047] The present invention also provides a lithium-ion battery, which is mainly composed of a negative electrode plate, an electrolyte, a separator and a metal lithium plate, and the negative electrode plate is the negative electrode plate of the lithium-ion battery described above.
[0048] The present invention also provides a tin selenide-nitrogen doped carbon nanotube composite material, which is prepared by the above-mentioned preparation method.
[0049] The present invention also proposes a negative electrode plate for a lithium-ion battery, which is composed of a negative electrode material, superconducting carbon, and a binder in a mass ratio of 80:10:10, and the negative electrode material is a tin selenide-nitrogen doped carbon nanotube composite material prepared by the above-mentioned preparation method or the above-mentioned tin selenide-nitrogen doped carbon nanotube composite material.
[0050] The present invention also provides a lithium-ion battery, which is mainly composed of a negative electrode plate, an electrolyte, a separator and a metal lithium plate, and the negative electrode plate is the negative electrode plate of the lithium-ion battery described above.
[0051] Example 1
[0052] This embodiment provides a method for preparing a tin selenide-nitrogen doped carbon nanotube composite material, comprising the following steps:
[0053] S1: Weigh 316mg KMnO4 and 158mg NH4Cl, and dissolve the manganese salt and ammonium salt in 60mL deionized water to prepare aqueous solutions, with concentrations of 0.033mol / L and 0.033mol / L respectively; under stirring, pour the ammonium salt aqueous solution into the manganese salt solution, continue stirring for 30min, transfer the mixed solution to a reactor, and place it in an oven for reaction; the reaction temperature is 200℃ and the reaction time is 24h. MnO2 nanowires are prepared.
[0054] S2: Weigh 200mg MnO2 nanowires and disperse them in 60mL of a mixed solution of water and ethanol, the volume ratio of water to ethanol is 1:1.67; the ratio of MnO2 nanowires to the mixed solution is 100mg:30mL; weigh 1800mg urea and add it to the mixed solution, the concentration of urea in the solution is 0.5mol / L; weigh 288mg K2SnO3·3H2O and add it to the mixed solution, the concentration of K2SnO3·3H2O in the solution is 0.016mol / L; continue stirring for 1h, transfer the mixed solution to a reactor, and place it in an oven for reaction; the reaction temperature is 170℃, and the reaction time is 2h. Tin dioxide-coated manganese dioxide MnO2@SnO2 nanowires are obtained.
[0055] S3: Weigh 242mg of tris(hydroxymethyl)aminomethane and dissolve it in 200mL of deionized water at a concentration of 0.01mol / L; weigh 200mg of MnO2@SnO2 nanocables and disperse them in the tris(hydroxymethyl)aminomethane aqueous solution; the ratio of MnO2@SnO2 nanocables to tris(hydroxymethyl)aminomethane solution is 100mg:100mL; weigh 100mg of dopamine hydrochloride and pour it into the mixed solution and stir it thoroughly; the mass ratio of MnO2@SnO2 nanocables to dopamine hydrochloride is 1:1; stir thoroughly for 4h. Obtain MnO2@SnO2@PDA nanocables.
[0056] S4: Weigh 200 mg of oxalic acid and dissolve it in 100 mL of deionized water to prepare an oxalic acid aqueous solution with a concentration of 0.5 mol / L; weigh 200 mg of MnO2@SnO2@PDA nanocrystals, pour the MnO2@SnO2@PDA nanocrystals into the oxalic acid solution and let it stand; the ratio of MnO2@SnO2@PDA nanocrystals to the oxalic acid aqueous solution is 100 mg:50 mL; let it stand for 2 hours. SnO2@PDA nanotubes are obtained.
[0057] S5: Weigh 100 mg SnO2@PDA nanotubes and 200 mg selenium powder respectively, mix the SnO2@PDA nanotubes and selenium powder, and then calcine the mixture in an inert atmosphere; the mass ratio of SnO2@PDA nanotubes to selenium powder is 1:2; the calcination is specifically to increase the temperature from room temperature to 350°C at a rate of 2°C / min, calcine for 2h; then increase the temperature to 700°C at a rate of 2°C / min, calcine for 2h. SnSe@NCNTs, a tin selenide-nitrogen doped carbon nanotube composite material, is obtained.
[0058] The tin selenide-nitrogen doped carbon nanotube composite material prepared in this example is prepared into a negative electrode sheet for a lithium ion battery, and then assembled into a lithium ion battery.
[0059] Figure 1 is the XRD (X-ray diffraction) spectrum of the SnSe@NCNTs composite material in Example 1, and the characteristic diffraction peaks at 21.5°, 25.2°, 26.5°, 29.3°, 30.4°, 31.1°, 37.8°, 40.6°, 41.4°, 43.3°, 43.5°, 44.3°, 47.1°, 47.3°, 49.1°, 49.7°, 51.0°, 52.0°, 52.5° and 54.5° correspond to SnSe (JCPDS The diffraction peaks of (101), (201), (210), (011), (111), (400), (301), (002), (102), (411), (020), (501), (112), (302), (212), (511), (221), (402), (312), (610) and (420) crystal planes of carbon nanotube No. 48-1224 are strong, proving that the prepared tin selenide-nitrogen doped carbon nanotube composite material has high crystallinity.
[0060] Figure 2 The SEM (scanning electron microscope) images of the SnSe@NCNTs composite material in Example 1, (a) to (d) are SEM images of SnSe@NCNTs at different magnifications, respectively. It can be seen from the figure that SnSe@NCNTs are one-dimensional hollow nanorod particles. These one-dimensional hollow nanorod particles are composed of nitrogen-doped carbon nanotubes coated with tin selenide (tin selenide is coated inside the nitrogen-doped carbon nanotubes), and the hollow structure is formed because the MnO2 nanowires are etched and removed by oxalic acid. Nitrogen-doped carbon nanotubes are produced by calcining, decomposing and carbonizing polydopamine in a hydrogen-argon mixed atmosphere.
[0061] Figure 3 The SnSe@NCNTs composite material in Example 1 is 0.1A·g in the voltage range of 0.01-3.0V. -1The charge and discharge curves under current density show that during the first discharge, the SnSe-N-doped CNT composite material has three long discharge platforms at 1.3-1.4V, 0.4-0.7V and 0.3-0.5V, representing Li + Embedded in the SnSe lattice, it is reduced to Sn and Li2Se, and Li + Alloying reaction with Sn to generate Li x Sn alloy. During the first charge, three charging platforms appeared at around 0.6V, 1.2V and 1.75V, which was mainly due to the oxidation reaction of Sn to generate SnSe. In the subsequent cycles, the charging platform of SnSe@NCNTs composite material did not change. The first discharge specific capacity and charge specific capacity of SnSe@NCNTs composite material were 1234.2mAh·g -1 and 887.9mAh·g -1 The corresponding coulombic efficiency and irreversible capacity are 71.93% and 346.3 mAh·g -1 .
[0062] Figure 4 The rate performance curve of SnSe@NCNTs and SnSe negative electrode materials in Example 1, the current density is 0.1A·g -1 ~2.0A·g -1 From the figure, we can see that when the current density is 0.1A·g -1 ,0.2A·g -1 , 0.5A·g -1 and 1.0A·g -1 When the discharge capacity of SnSe@NCNTs is 1312.5mAh·g -1 、581.8mAh·g -1 、447.2mAh·g -1 and 338.0mAh·g -1 Even if the current density reaches 2.0A·g -1 When SnSe@NCNTs electrode material is -1 When the current density is increased from 2.0A·g -1 Reduced to 0.1A·g -1 When the SnSe@NCNTs is 2.5×10·m3, the specific capacity of SnSe@NCNTs can be restored to 445.2 mAh·g -1 After 50 cycles, the discharge capacity of SnSe@NCNTs remained stable at 470 mAh g -1The above results show that the structure of the SnSe@NCNTs electrode material is not significantly damaged at high current density, and the structural integrity can still be maintained, showing very good rate performance. However, at the same current density, the discharge capacity of the SnSe negative electrode material decays very quickly. Moreover, as the current density increases, the discharge capacity decay of SnSe will become more serious. When the current density increases to 2.0A·g -1 When the discharge capacity of SnSe is only 8.3 mAh g -1 When the current density is reduced to 0.1A·g -1 Although the discharge capacity of SnSe can be restored to 450 mAh g -1 However, as the number of cycles increases, the discharge capacity will gradually decay. Therefore, compared with SnSe anode materials, SnSe@NCNTs has better rate performance.
[0063] Figure 5 The cycle performance diagram of SnSe@NCNTs and SnSe negative electrode materials in Example 1. As can be seen from the figure, at 1.0 A·g -1 At a current density of 1.34 W, the first discharge capacity of SnSe@NCNTs electrode material is 1119.1 mAh g -1 , the charging capacity is 776.8mAh·g -1 The first charge and discharge efficiency is 69.41%. After 1000 cycles, the SnSe@NCNTs electrode material can still release 422.3 mAh g -1 The first discharge capacity of SnSe negative electrode material is 1092.5 mAh g -1 , the charging capacity is 574.6mAh·g -1 The first charge and discharge efficiency is 52.6%. As the number of cycles increases, the capacity of the SnSe electrode material decays rapidly. After 200 cycles, the discharge capacity of the SnSe electrode material is only 76.8 mAh g -1 Obviously, SnSe@NCNTs exhibit higher specific capacity and better cycle stability than SnSe anode materials.
[0064] Example 2
[0065] This embodiment provides a lithium-ion battery negative electrode plate and a lithium-ion battery. The negative electrode material of the lithium-ion battery negative electrode plate is the tin selenide-nitrogen-doped carbon nanotube composite material SnSe@NCNTs described in Example 1, and the negative electrode plate of the lithium-ion battery is the lithium-ion battery negative electrode plate.
[0066] The specific preparation method is as follows:
[0067] (1) Preparation of negative electrode sheet. Weigh the negative electrode material SnSe@NCNTs, superconducting carbon and binder PVDF in a mass ratio of 80:10:10 and place them in a high-energy ball mill. Weigh deionized water in a mass ratio of PVDF / deionized water of 1:40 and add it to the high-energy ball mill. Mill at a speed of 300 r / min for 30 minutes to obtain a uniformly mixed slurry. Finally, the obtained slurry is evenly coated on the copper foil, and the surface density is controlled to an average of 0.6 mg / cm 2 The obtained electrode was placed in a vacuum drying oven and vacuum dried at 120°C for 12 h. After naturally cooling to room temperature, it was cut into discs with a diameter of 15 mm, weighed, and transferred to a glove box.
[0068] (2) Lithium-ion battery assembly. The lithium-ion battery assembly process described in this embodiment is completed in a high-purity argon glove box, and the moisture content in the glove box is less than 0.1ppm and the oxygen content is less than 0.1ppm. The disc prepared in step (1) is used as the negative electrode, Celgard 2400 with a diameter of 19mm is used as the diaphragm, the electrolyte is a mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) with a concentration of 1M lithium hexafluorophosphate (LiPF6) (the volume ratio of ethylene carbonate and dimethyl carbonate is 1:1), and a metal lithium sheet with a diameter of 15.6mm is used as the counter electrode. The 2032 button battery is assembled, and the press pressure is 1000psi.
[0069] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a tin selenide-nitrogen doped carbon nanotube composite material, characterized in that: The following steps are involved: S1: weighing manganese salt and ammonium salt, respectively preparing aqueous solutions, then pouring the ammonium salt solution into the manganese salt solution, stirring thoroughly, heating in a reactor to react, and obtaining MnO2 nanowires; S2: dispersing the MnO2 nanowires in a mixed solution of water and ethanol, respectively adding a urea aqueous solution and a stannate aqueous solution, stirring sufficiently, and heating in a reactor to react, thereby obtaining MnO2@SnO2 nanowires; S3: dispersing the MnO2@SnO2 nanocable in a tris(hydroxymethyl)aminomethane aqueous solution, adding dopamine hydrochloride, stirring thoroughly, and centrifuging to obtain a MnO2@SnO2@PDA nanocable; S4: dispersing the MnO2@SnO2@PDA nanocables in an oxalic acid solution, allowing the solution to stand, and centrifuging to obtain SnO2@PDA nanotubes; S5: Grind and mix the SnO2@PDA nanotubes and Se powder according to a mass ratio, and calcine them in a mixed atmosphere of H2 / Ar to obtain a tin selenide-nitrogen doped carbon nanotube composite material.
2. The method for preparing a tin selenide-nitrogen doped carbon nanotube composite material according to claim 1, characterized in that: In step S1, the manganese salt is at least one of manganese nitrate Mn(NO3)2, manganese chloride MnCl2, manganese carbonate MnCO3, manganese acetate Mn(CH3COO)2, manganese sulfate MnSO4, manganese hypophosphite Mn(PO2)2, manganese perchlorate Mn(ClO4)2, potassium permanganate KMnO4 and manganese acetylacetonate Mn[CH3COCH=C(O)CH3]2; the ammonium salt is at least one of ammonium sulfate (NH4)2SO4, ammonium carbonate (NH4)2CO3, ammonium nitrate NH4NO3, ammonium fluoride NH4F, ammonium chloride NH4Cl, ammonium bromide NH4Br, ammonium iodide NH4I, ammonium bicarbonate NH4HCO3 and ammonium bisulfate NH4HSO4; the manganese salt concentration in the manganese salt solution is 0.02-0.05 mol / L; the ammonium salt concentration in the ammonium salt solution is 0.02-0.05 mol / L; the temperature of the heating reaction is 160-220 ℃, time is 8~36 h.
3. The method for preparing a tin selenide-nitrogen doped carbon nanotube composite material according to claim 1, characterized in that: In step S2, the mixed solution is a mixed solution of water and ethanol in a volume ratio of 1:1 to 1:3; the ratio of the MnO2 nanowires to the mixed solution is 100 mg:20 to 40 mL; the concentration of urea in the reaction solution of the heating reaction is 0.2 to 0.8 mol / L; the concentration of stannate in the reaction solution of the heating reaction is 0.01 to 0.03 mol / L; the temperature of the heating reaction is 150 to 200 °C, and the time is 1 to 3 h.
4. The method for preparing a tin selenide-nitrogen doped carbon nanotube composite material according to claim 1, characterized in that: In step S3, the mass ratio of the MnO2@SnO2 nanocable to dopamine hydrochloride is 1:3~3:1; the ratio of the MnO2@SnO2 nanocable to tris(hydroxymethyl)aminomethane solution is 100 mg:50~200 mL, and the concentration of the tris(hydroxymethyl)aminomethane solution is 0.005~0.05 mol / L; and the sufficient stirring time is 2~24 h.
5. The method for preparing a tin selenide-nitrogen doped carbon nanotube composite material according to claim 1, characterized in that: In step S4, the concentration of the oxalic acid solution is 0.2-1.2 mol / L; the ratio of the MnO2@SnO2@PDA nanocable to the oxalic acid solution is 100 mg:50-200 mL; and the standing time is 0.5-12 h.
6. The method for preparing a tin selenide-nitrogen doped carbon nanotube composite material according to claim 1, characterized in that: In step S5, the roasting is specifically: The temperature was raised from room temperature to 200-400 °C at a rate of 1-10 °C / min, and the calcination was performed for 1-4 h. The temperature was then raised from 200-400 °C to 600-900 °C at a rate of 1-10 °C / min, and the calcination was performed for 1-4 h.
7. The method for preparing a tin selenide-nitrogen doped carbon nanotube composite material according to claim 1, characterized in that: In step S5, the volume ratio of H2 to Ar in the mixed atmosphere is 1:
9.
8. A tin selenide-nitrogen doped carbon nanotube composite material, characterized in that: The tin selenide-nitrogen doped carbon nanotube composite material is prepared by the method for preparing a tin selenide-nitrogen doped carbon nanotube composite material according to any one of claims 1 to 7.
9. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate is composed of a negative electrode material, superconducting carbon, and a binder in a mass ratio of 80:10:
10. The negative electrode material is a tin selenide-nitrogen-doped carbon nanotube composite material prepared by the preparation method of a tin selenide-nitrogen-doped carbon nanotube composite material according to any one of claims 1 to 7, or the tin selenide-nitrogen-doped carbon nanotube composite material according to claim 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode plate, an electrolyte, a separator and a metal lithium plate, and the negative electrode plate is the negative electrode plate of the lithium-ion battery according to claim 9.